HUBUNGAN POLA MAKAN DENGAN KEJADIAN DIABETES MELLITUS DI PUSKESMAS NAMORAMBE KABUPATEN DELI SERDANG - yessica tarihoran; Dewi F Silaban (Jurnal Penelitian Keperawatan Medik, 2022)
Diabetes Mellitus (DM) is a degenerative’s disease which really has been associated with Diet. Diet is depiction abaout the various, amount and composition of foodstuff to some one who eaten everyday. The change of life style shifted from traditional Diet that contain more carbohydrate and fibre of vegetables to the modern Diet in the instaneous form in diet with hinger fat, protein, sugar, sald and e few fibre and result in many disease Inclucde DM. According to WHO, Indonesian is in 5th rank of number of patient with DM in prevalence 1,2% - 2,3% of the total population. The purpose of the research is to know about the relationship on Diet with Diabetes Mellitus type 2 in the Puskesmas Biru – Biru regency of Deli Serdang. This research is a descriptive analytic with cross sectional design (study cut latitude). The sampling method used to accidental sampling that consist of 44 Respondents. Research instruments used to quistionnaries study consisted of 20 questions. The answer of questions which there are in kuesioner, the data that collected is being analized using the chi - square test and counted by SPSS program. This result of this research which is gain the trusted level of 95 % show value p=0,001. This p value is smaller than α = 0,05. The conclusion of this research is showed that a significant relationship on diet with Diabetes Mellitus type-2 in the Puskesmas Namorambe, regency of Deli Serdang. The important suggestion of the medical staff and paramedic and nutritonist is to provide the patient with DM with information who visit Puskesmas Namorambe, to regualte the diet in good condition.